Laboratory development of an RNA quantitative RT-PCR assay reporting in international units for hepatitis D virus - Osiowy, Carla; Day, Jacqueline; Lee, Emma R. (Frontiers in Microbiology, 2024)
IntroductionChronic hepatitis D virus (HDV) is associated with rapid progression to severe liver disease. Co-infection with HDV and hepatitis B virus is likely underdiagnosed due to challenges in diagnostic test availability and standardization. With new HDV antiviral options, HDV RNA quantification is essential for understanding the patient response to treatment. To this end, a quantitative real-time reverse transcription PCR (qRT-PCR) assay utilizing synthetic RNA calibrators and a conversion factor to quantify HDV RNA in WHO international standard units (IU/mL) was developed and validated.MethodsqRT-PCR primers and probes were selected within the ribozyme region. Thermocycling conditions and reactions were optimized. Synthetic RNA transcripts were prepared as quantification standards and calibrators. Transcript dilutions (log10 8 to log10 1 copies/μL) were calibrated against the WHO standard and a conversion factor calculated to convert copies/μL to IU/mL. Assay validation and evaluation was conducted, including use of specimens from 8 HDV genotypes and comparison to a commercial assay.ResultsThe assay lower limit of detection was determined by probit analysis to be 11 IU/mL (8.63–15.78 95% CI). Inter- and intra-assay coefficient of variation analysis showed 96.6% precision and 90.6% accuracy. A conversion factor of 16.5 was used to convert copies/μL to IU/mL. All 8 HDV genotypes were quantified by the assay and commercial assay comparison showed good agreement.DiscussionThe developed assay has clinical utility for the sensitive and specific quantitative monitoring of HDV RNA, appropriate for medium to high throughput laboratories.